2023
DOI: 10.3389/fpsyt.2023.1087909
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness on social media addiction among Chinese college students: A serial mediation model

Abstract: IntroductionThe COVID-19 pandemic has exacerbated social media addiction (SMA), making it urgent to find effective interventions for social media addiction. Evidence has shown that mindfulness might be an effective intervention for social media addiction. However, psychological mechanisms by which mindfulness reduce social media use remain unclear. Here, we further addressed this issue to examine whether attentional control and fear of missing out (FOMO) mediate the relationship between mindfulness and SMA.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Regarding anxiety level, in a cross-sectional study, the mediating effects of self-reported shifting and focusing attentional control between dispositional mindfulness and anxiety symptoms were validated in college students (MacDonald and Olsen 2020). This finding aligns with Goodall, Brodie, and Schwannauer (2020) and Chang et al (2023), reporting an indirect mediation effect of attentional control between dispositional mindfulness and attachment anxiety or social media addiction. Regarding depression level, Kou et al (2023) demonstrated that improvements in attentional bias towards sad faces partially mediated the effect of mindfulness training on depression outcomes at post-intervention.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding anxiety level, in a cross-sectional study, the mediating effects of self-reported shifting and focusing attentional control between dispositional mindfulness and anxiety symptoms were validated in college students (MacDonald and Olsen 2020). This finding aligns with Goodall, Brodie, and Schwannauer (2020) and Chang et al (2023), reporting an indirect mediation effect of attentional control between dispositional mindfulness and attachment anxiety or social media addiction. Regarding depression level, Kou et al (2023) demonstrated that improvements in attentional bias towards sad faces partially mediated the effect of mindfulness training on depression outcomes at post-intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with these findings, Judah et al (2014) found a strong negative correlation between attentional control levels and symptoms of depression and anxiety among college students using the ACS. The mediating role of attentional control between mindfulness and reductions in anxiety or depression levels was validated in various cross-sectional designs (Chang et al 2023;MacDonald and Olsen 2020;Yu et al 2018).…”
mentioning
confidence: 99%